2005
DOI: 10.1289/ehp.7386
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Occupational Exposure on Lead Levels in Women

Abstract: In 1994, 207 women participated in a study designed to examine the effects of occupational exposure and various lifestyle factors on bone and blood lead levels. In vivo measurements of Pb concentrations in tibia were performed by X-ray fluorescence. All 108 former smelter employees and 99 referents provided blood samples and answered a questionnaire on lifestyle characteristics and the relevant medical history. Lead concentrations in tibia and blood were significantly higher in the exposed group. The differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 18 publications
(13 reference statements)
7
62
0
3
Order By: Relevance
“…The bone lead level is higher in men than in women 25,44) . For example, the lead concentration in tibial bone was reported to be 9.7 µ g/g higher in men than in women 45) .…”
Section: Storage and Release Of Bone Lead Into The Bloodstream In Womenmentioning
confidence: 88%
See 2 more Smart Citations
“…The bone lead level is higher in men than in women 25,44) . For example, the lead concentration in tibial bone was reported to be 9.7 µ g/g higher in men than in women 45) .…”
Section: Storage and Release Of Bone Lead Into The Bloodstream In Womenmentioning
confidence: 88%
“…Like many toxic substances, the health risk assessment of lead has largely been based on data from exposed men 23) , and women have mainly been investigated in mixed-gender studies. However, studies of men exposed to lead have many limitations when trying to understand the effects in women because of differences in organs, hormones, and other aspects such as lead metabolism and biokinetics [24][25][26] , dose-response relationships, thyroid function, and accumulation of lead in the liver [27][28][29] .…”
Section: Gender and Lead Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Kemal et al [28] in the analysis to assess the impact of sex on urinary delta-ALA levels among workers in lead acid battery repair units of transport service enterprises in Ethiopia, failed to show any significant sex-related differences, although levels in males tended to increase than females. Interestingly, Popovic et al recently reported very different long-term lead kinetics between men and women, with pre-menopausal women appearing to retain lead more avidly or release lead more slowly compared to postmenopausal women and men [30].…”
Section: Discussionmentioning
confidence: 99%
“…We defined high lead content to be >1.5 mcg/serving, based on the 1999 California criteria for acceptable lead levels of <1.5 mcg/serving of natural calcium supplement. 27 We stratified the analysis by sex, given different potential health concerns related to low-level lead exposure and because men and women typically use different types of herbs, 28 have different lead exposures, 29 and may metabolize lead differently.…”
mentioning
confidence: 99%